SARS-CoV-2 infection induces a pro-inflammatory cytokine response through cGAS-STING and NF-κB - Christopher J. Neufeldt; Berati Cerikan; Mirko Cortese; Jamie Frankish; Ji-Young Lee; Agnieszka Plociennikowska; Florian Heigwer; Vibhu Prasad; Sebastian Joecks; Sandy S. Burkart; David Y. Zander; Baskaran Subramanian; et al. (Communications Biology, 2022)
Neufeldt et al. evaluate transcriptional and cytokine secretion profiles of cells and patient sera following SARS-CoV-2 infection and detect distinct upregulation of inflammatory cytokines. They also demonstrate that this upregulation is mediated by cGAS-STING and NF-κB signalling, which could provide a potential avenue for the development of future therapies against SARS-CoV-2.